1987
DOI: 10.1002/ana.410210113
|View full text |Cite
|
Sign up to set email alerts
|

4‐Aminopyridine improves clinical signs in multiple sclerosis

Abstract: Twelve temperature-sensitive male patients with multiple sclerosis and 5 normal men were monitored before, during, and after the intravenous injection of 7 to 35 mg of 4-aminopyridine (4-AP) in 1- to 5-mg doses, every 10 to 60 minutes. Static quantitative perimetry, flicker-fusion frequency, visual acuity, and videotaped neurological examinations were performed. Ten of the 12 patients showed mild to marked improvement. Vision improved in 7 patients, oculomotor function in 5, and motor function (power, coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 31 publications
2
65
0
Order By: Relevance
“…4-aminopyridine (4-AP), a potassium channel blocker, has been used to temporarily relieve the neurological symptoms in MS patients at a dose 1000 times lower than that required to restore electrical transmission in demyelinated fibers. 60 Evidence has shown that low-dose 4-AP treatment enhances synaptic transmission by increasing synaptic vesicle release. 61 On the other hand, both dendritic beading and the loss of syn- The marked reduction in synaptophysin and synapsin I immunoreactivity was well correlated with EAE severity.…”
Section: Discussionmentioning
confidence: 99%
“…4-aminopyridine (4-AP), a potassium channel blocker, has been used to temporarily relieve the neurological symptoms in MS patients at a dose 1000 times lower than that required to restore electrical transmission in demyelinated fibers. 60 Evidence has shown that low-dose 4-AP treatment enhances synaptic transmission by increasing synaptic vesicle release. 61 On the other hand, both dendritic beading and the loss of syn- The marked reduction in synaptophysin and synapsin I immunoreactivity was well correlated with EAE severity.…”
Section: Discussionmentioning
confidence: 99%
“…One subject demonstrated a clear gait improvement that was proven to be reversible. The quality of the gait improvement was not described [Stefoski et al 1987].…”
Section: Immediate-release 4-aminopyridinementioning
confidence: 99%
“…Similar to neurotrauma, multiple sclerosis has a long history of clinical testing of 4-AP [50][51][52][53][54][55][56][57][58][59][60][61] . Recently, a series of carefully designed clinical trials have provided significant improvement in walking ability of multiple sclerosis patients [43,[62][63][64] .…”
Section: The Effects Of 4-ap In Human Testingmentioning
confidence: 99%